Referral Reward Program Influence on Customer Engagement: The Role of Reward Type and Task Complexity - Do Minh, Hoang; Tran Hoai, Nam (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Referral reward programs have become a central and cost-effective strategy for customer acquisition in digital marketing. This study examines the direct and interactive effects of reward type (monetary vs. nonmonetary) and task complexity (low vs. high) on customer engagement in referral reward programs. Using real-world engagement data, we analyze 541 referral program posts from 13 brands. Applying Multivariate Analysis of Covariance (MANCOVA), the results indicate that nonmonetary rewards consistently elicit higher customer engagement than monetary rewards, while high task complexity significantly dampens engagement. Importantly, the findings uncover a meaningful interaction effect: when task complexity is low, monetary and nonmonetary rewards generate comparable levels of engagement; however, as task complexity increases, nonmonetary rewards become markedly more effective than monetary rewards in driving engagement. Through integrating reward design with task-related cost considerations, this study offers a more nuanced understanding of how referral reward programs influence customer engagement in digital environments. The study advances the referral marketing literature by providing empirical evidence from real in-market social media campaigns and by identifying task complexity as a critical boundary condition that shapes the effectiveness of reward types. Overall, the findings underscore the strategic importance of aligning reward types with task demands to enhance engagement outcomes and strengthen consumer–brand relationships in competitive digital markets.